Spatially distributed modelling of surface water-groundwater exchanges during overbank flood events – a case study at the Garonne River. (August 2016) - Bernard-Jannin, Léonard; Brito, David; Sun, Xiaoling; Jauch, Eduardo; Neves, Ramiro; Sauvage, Sabine; Sánchez-Pérez, José-Miguel
Highlights: A distributed hydrodynamic model is applied to a floodplain section. The model includes coupled subsurface and surface flows modelling. Infiltration and exfiltration exhibit strong spatiotemporal variations. Infiltration from overbank flow is important for alluvial aquifer recharge. Abstract: Exchanges between surface water (SW) and groundwater (GW) are of considerable importance to floodplain ecosystems and biogeochemical cycles. Flood events in particular are important for riparian water budget and element exchanges and processing. However SW-GW exchanges present complex spatial and temporal patterns and modelling can provide useful knowledge about the processes involved at the scale of the reach and its adjacent floodplain. This study used a physically-based, spatially-distributed modelling approach for studying SW-GW exchanges. The modelling in this study is based on the MOHID Land model, combining the modelling of surface water flow in 2D with the Saint-Venant equation and the modelling of unsaturated groundwater flow in 3D with the Richards' equation. Overbank flow during floods was also integrated, as well as water exchanges between the two domains across the entire floodplain. Conservative transport simulations were also performed to study and validate the simulation of the mixing between surface water and groundwater. The model was applied to the well-monitored study site of Monbéqui (6.6 km²) in the Garonne floodplain (south-west France) for a five-month period and was able to represent the hydrology of the study area. Infiltration (SW to GW) and exfiltration (SW to GW) were characterised over the five-month period. Results showed that infiltration and exfiltration exhibited strong spatiotemporal variations, and infiltration from overbank flow accounted for 88% of the total simulated infiltration, corresponding to large flood periods. The results confirmed that overbank flood events played a determinant role in floodplain water budget and SW-GW exchanges compared to smaller (below bankfull) flood events. The impact of floods on water budget appeared to be similar for flood events exceeding a threshold corresponding to the five-year return period event due to the study area's topography. Simulation of overbank flow during flood events was an important feature in the accurate assessment of exchanges between surface water and groundwater in floodplain areas, especially when considering large flood events.